A nanocatalyst network for electrochemical reduction of CO2 over microchanneled solid oxide electrolysis cells - Yu, L.; Wang, J.; Hu, X.; Ye, Z.; Buckley, C.; Dong, Dehua (Elsevier Inc., 2018)
A nanocatalyst network has been successfully prepared over the internal surface of Ni-based cathode support with a microchanneled structure via an impregnation process. Through numerous microchannels within the cathode support, a catalyst precursor solution was effectively delivered to the interface between cathode and electrolyte, resulting in the formation of the nanocatalyst network in the cathode reaction zone and therefore decreased degradation rate during CO 2 electrolysis. After four coatings, the robust nanocatalyst network was formed to produce the least degradation, and further catalyst coatings caused concentration polarization.